Is buffalo enamel a suitable substrate for bond strength tests? - Baia JCP; Ribeiro MES; Nogueira BCL; Lima RR; Silva e Souza Júnior MH; Loretto SC (Dove Medical Press, 2019)
Juliana Costa Pereira Baia,1 Mara Eliane Soares Ribeiro,1 Bárbara Catarina Lima Nogueira,1 Rafael Rodrigues Lima,2 Mário Honorato da Silva e Souza Júnior,1 Sandro Cordeiro Loretto1 1Department of Restorative Dentistry, UFPA – Federal University of Pará, Belém, PA, Brazil; 2Laboratory of Structural and Functional Biology, UFPA – Federal University of Pará, Belém, PA, Brazil Aim: The aim of this study was to compare the bonding strength of dental materials in buffalo (Bubalus bubalis var. kerebau), bovine, and human enamel and the susceptibility of these substrates in acid etching.Materials and methods: A total of 20 human third molars, 20 bovine incisors, and 20 buffalo incisors were used in a mechanical assay of microshear. The substrates were demineralized via conditioning with 37% phosphoric acid, and the ultra-morphological pattern of each substrate was analyzed by scanning electron microscopy.Results: The results showed that there was no significant difference in adhesive bonding strength values between buffalo and human enamel (P≥0.05), with a fracture pattern of mixed type for all experimental groups.Conclusion: The results indicate that buffalo enamel is similar to human dental substrate in tests of adhesive bonding strength and also show a similar behavior in the acid conditioning of the enamel. Keywords: dental enamel, shear strength, dental acid etching, scanning electron microscopy